HYBRIDISING EMPLOYEE PARTICIPATION IN EMERGING ECONOMIES: A SPECIAL ECONOMIC ZONES (SEZ)–CULTURE–TECHNOLOGY FRAMEWORK IN CHINA - Wang , Yajuan; Parasuraman, Balakrishnan; Yajid, Adi Aizat (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This study examines the evolution and localisation of employee participation (EP) in Special Economic Zones (SEZs) in China, focusing on the interplay of institutional adaptation, cultural buffering, and technical participation competence. Using a qualitative multi-case design involving six private enterprises from manufacturing, technology, and service sectors, data were collected through semi-structured interviews, document analysis, and non-participant observation. The findings reveal three dominant participation forms—institutionalised, technology-enabled, and culturally embedded—and identify distinct archetypes that reflect differences in ownership structure, industry context, and technological readiness. The analysis demonstrates that cultural norms mediate the effectiveness of formal EP mechanisms, while employees’ digital skills significantly influence participation depth in Industry 4.0 contexts. The study advances EP theory by integrating cultural and technological dimensions into institutional frameworks and offers practical insights for managers and policymakers seeking to design contextually appropriate participation strategies in emerging economies.